1962
DOI: 10.1037/h0042636
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal rigidity as a measure of creativity in gifted children.

Abstract: The performance of 68 academically talented elementary school children on a battery of verbal and nonverbal creativity tests was correlated with performance on a paper and pencil test purporting to measure attitudinal rigidity. A moderate negative relationship (r = -.41) was found to exist between rigidity and verbal creativity only. Investigation of the relationship of chronological age, intelligence, and sex indicated that while neither sex nor intelligence were significant factors, chronological age appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

1964
1964
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Other researchers have investigated the relationship between creativity and risk taking using related but indirect measures. Fleming and Weintraub (1962) , for instance, found an inverse relationship between rigidity and intolerance of ambiguity as a measure of risk and creativity, in elementary school children. Similarly, Kurtzman (1967) measured adventurousness as a personality characteristic and used several tests from the kit of reference tests for cognitive factors to measure creativity ( Ekstrom et al, 1976 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have investigated the relationship between creativity and risk taking using related but indirect measures. Fleming and Weintraub (1962) , for instance, found an inverse relationship between rigidity and intolerance of ambiguity as a measure of risk and creativity, in elementary school children. Similarly, Kurtzman (1967) measured adventurousness as a personality characteristic and used several tests from the kit of reference tests for cognitive factors to measure creativity ( Ekstrom et al, 1976 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among sixth-grade children, Fleming and Weintraub (1962) found significant negative relationships between the measures of originality, fluency, and flexibility and the measures of rigidity. Encouraging evidences of concurrent validity for the Torrance tests of creative thinking have also been derived from studies with adults, using the same test tasks that are administered to children.…”
Section: Childrenmentioning
confidence: 86%
“…Weisberg and Springer (1961) found that gifted preadolescents identified by the tests as creative, compared with their equally gifted (as measured by tests of intelligence) peers were rated significantly higher on: strength of self-image, ease of early recall, humor, self awareness, uneven ego development, unconventional responses, fanciful and imaginative treatment of ink blots, independence from environmental influences, and readiness to respond emotionally to the environment. Fleming and Weintraub (1962) found a negative relationship between scores on the creative thinking tests and rigidity. Lieberman (1965) found significant relationships between creativity scores and measures of playfulness among kindergarten children.…”
Section: Content Validitymentioning
confidence: 89%